A Study on Role of Narcissistic Personality Traits Towards Exposure to Security Risk in Social Media Networking Sites in India - B, LEELESH SUNDARAM.; R, SORNALAKSHIMI R.; GAYATHRI, R.; PRIYA, V. VISHNU (The journal of contemporary issues in business and government, 2020)
India has been popular on global outreach due to its encouragement in the Information innovation industry and as a result of the huge number of Indian I.T. experts working abroad. In this juncture various offences related to cyber network and social networking sites in respect of security have also increased at a great deal. The rate of cyber security offences focusing on social networking sites is directly proportional to rate of social networking site users. It could be understood that exposure to security risk in social media and networking sites is increasing day by day at an alarming rate. In Spite of the recent amendment in criminal law and Information technology offences and chances of victimhood could not be reduced. an ambiguity prevails in respect to the chances of exposure to risk in the cases of interchangeable characters. This ambiguity tends to be gleamed in the ambit of psychiatric jurisprudence in reference to Narcissistic personality traits, as it is a well founded principle that every perpetrator of cyber crime through social media networking sites suffer due to narcissistic personality disorder. Thus this research is carried out with an aim of identifying Narcissistic Personality Traits towards Exposure to security Risk in Social media Networking sites in India. By virtue of an empirical study with a sample size of 253 determined by convenient sampling through an open sample frame statistically studied with help of graphs, pie charts, Pearson correlation, Mann Whitney U test, independent t test and Kendall's tau_b test, the study was able to find out that individuals with narcissistic personality traits are not exposed to security risk arising out of computer oriented and related crimes compared to individuals with low levels of narcissistic personality traits. The female population is more prone to the security risk compared to the male population due to the difference in the level of narcissistic personality traits among the 2 genders.